Solve for b 7(b-1)=49

Math
7(b-1)=49
Divide each term by 7 and simplify.
Tap for more steps…
Divide each term in 7(b-1)=49 by 7.
7(b-1)7=497
Cancel the common factor of 7.
Tap for more steps…
Cancel the common factor.
7(b-1)7=497
Divide b-1 by 1.
b-1=497
b-1=497
Divide 49 by 7.
b-1=7
b-1=7
Move all terms not containing b to the right side of the equation.
Tap for more steps…
Add 1 to both sides of the equation.
b=7+1
Add 7 and 1.
b=8
b=8
Solve for b 7(b-1)=49

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top